Challenge in Diagnosis of Eczema Herpeticum in Rural Area in East Nusa Tenggara: a Case Report - Nur Aida Oktasari; Adisty Ridha Damasuri; Indah Sari; Anita Tanuwijaya (Syntax Idea)
Eczema herpeticum is an infection caused mostly by the herpes simplex virus which arises from an impaired skin barrier that may have a life-threatening bacterial complication. This case report unfolds the clinical reasoning behind diagnosing and treating eczema herpeticum in a rural area in East Nusa Tenggara, Indonesia, that has limited healthcare facilities in favor of recovery without any sequelae. We describe a 5-month-old girl who has dry skin with acute extensive itchy vesicles and papulopustular with crusts starting from the face down to the neck, back, and extremities that worsened even after receiving antibiotics yet showed improvement after receiving acyclovir.